Acute Deterioration in Pleomorphic Xanthoastrocytoma in a Child - Roka, YB; Pandey, SR; Roka, N (Journal of Nepal Paediatric Society, 2015)
Pleomorphic Xanthoastrocytoma (PXA) occur in less than 1 % of cases and usually present in the second decade. They present with seizures, focal deficits, intratumoral bleed and rarely with malignant transformation. The few cases that have been reported with acute deterioration in PXA have been secondary to intratumoral bleed. We present a case of PXA in a child that deteriorated secondary to high intracranial pressure which was managed successfully. J Nepal Paediatr Soc 2014;34(3):233-235 DOI: http://dx.doi.org/10.3126/jnps.v34i3.10098